Building Online Learning Communities Utilizing Adult Learning Andragogical Principles - Yaxin Zheng; Susan J Barcinas (Adult Education Research Conference, 2016)
This exploratory practice-based project considers how current online pedagogical practices centered on creating a learning community (Palloff & Pratt, 2007) integrate with principles of designing and implementing adult learner friendly learning experiences (Knowles, 1984) in online courses.
Keywords: Andragogy; Online Learning; Learning Communities